Consequences for Culpable Auditors - Krishnan, Jagan; Li, Meng; Mehta, Mihir N.; Park, Hyun Jong (Journal of Accounting Research, 2025)
ABSTRACT We present the first comprehensive descriptive evidence on the labor market and personal consequences for audit professionals in the United States who are named in SEC or PCAOB enforcement actions. Three key findings emerge. First, between 38% and 73% of culpable auditors depart from their firms within one year after the enforcement event. These departure rates are three to four times higher compared with a sample of non‐culpable auditors. Second, 83% of culpable auditors departing from Big 4 accounting firms exit the profession, compared with 58% of a departing non‐culpable comparison group. In contrast, about 77% of the culpable auditors leaving non–Big 4 accounting firms remain in public accounting, compared with 51% of a departing non‐culpable comparison group. Third, using novel data on personal real estate holdings, we find that culpable auditors do not appear to engage in markedly different transactions around enforcement compared with a comparison sample of non‐culpable individuals.